2019
DOI: 10.30773/pi.2018.11.07
|View full text |Cite
|
Sign up to set email alerts
|

Mature Defense Mechanisms Affect Successful Adjustment in Young Adulthood-Adjustment to Military Service in South Korea

Abstract: Objective A defense mechanism is an automatic psychological process necessary for successful adaptation. It reflects adaptive capacity. The purpose of this study is to explore the relationship between the adaptation ability of individuals who face mandatory military service and the pattern of defense mechanisms. Methods The subjects were 69 men (21.4±2.2 years) who expressed psychological difficulties in three military service situations. Control group was 36 men (24.0±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…These mechanisms appear to moderate the relationship between other risk factors-such as knowing someone with COVID-19-and symptoms of distress and PTSD. The key role of implicit emotion regulation in dealing with stressful life events is particularly important for vulnerable people, such as patients with chronic physical and mental illness (51)(52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms appear to moderate the relationship between other risk factors-such as knowing someone with COVID-19-and symptoms of distress and PTSD. The key role of implicit emotion regulation in dealing with stressful life events is particularly important for vulnerable people, such as patients with chronic physical and mental illness (51)(52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies (e.g., Soldz & Vaillant, 1998) have found that as participants grew older, the use of immature defence mechanisms decreased, and the use of mature defence mechanisms increased. Nam et al's (2019) study examined the use of mature defence mechanisms among military servicemen in South Korea. The control group consisted of 36 men who reported no negative psychological effects as a result of military service, and the experimental group was comprised of 69 men who experienced psychological impediments related to military service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The maturity of such defence mechanisms is positively associated with adaptability and negatively associated with psychopathology (Nam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In an Italian cohort, different levels of defenses were related to varying degrees of adaptation to stress ( Di Giuseppe et al., 2020c ). In addition, emotional regulation is of utmost importance during stressful times, particularly among vulnerable groups, such as patients suffering from physical or mental illnesses ( Di Giuseppe et al., 2020c ; Zilcha-Mano, 2021 ; Boldrini et al., 2020 ; Di Giuseppe et al., 2020 ; Martino et al., 2020a ; Martino et al., 2020 ; Nam et al., 2019 ). One study of defense mechanisms and coping strategies found that coping mechanisms, a positive attitude, and mature defense mechanisms negatively correlated with perceived stress ( Gori, Topino & Di Fabio, 2020 ).…”
Section: Introductionmentioning
confidence: 99%